Lab-on-a-molecule and multi-analyte sensing - Magri, David C. (Frontiers in Chemistry, 2024)
The concept of a lab-on-a-molecule, proposed just short of two decades ago, has captured the imagination of scientists. Originally proposed as an AND logic gate driven by three chemical inputs as a direct way of detecting congregations of chemical species, the definition of what constitutes a labon-a-molecule has broadened over the years. In this review, molecules that detect multiple analytes by fluorescence, among other techniques, are reviewed and discussed, in the context of molecular logic and multi-analyte sensing. The review highlights challenges and suggestions for moving the frontiers of research in this field to the next dimension.